COVID-19 pandemic: insights into human behaviour - Shah, Anuradha Kunal; Ravichandran, Prabhadevi; Ravichandran, Prabhu (International Journal Of Community Medicine And Public Health, 2020)
COVID-19 has placed an overwhelming burden on health care systems and authorities. In the absence of a vaccine or definitive treatment, widespread social and behavioral changes are critical in mitigating the impact. These are highly influenced by risk perception by the public, protective and preparedness behaviors, and effective communication. Here we have highlighted some of the commonly seen human behaviors during a pandemic crisis.